Les enjeux de la réforme du Sénat - Dion, Léon (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
The proposed reform of the Senate has not originated from widespread public demand but from the determination of Prime Minister Trudeau to proceed with the revision of the Canadian Constitution without further delay. In view of the refusal of the government of Quebec to sign and recognize the Constitution Act, one may question the advisability of such a move. The author proposes that before proceeding to a reform of the Senate, one should amend the constitutional revision procedure adopted in 1982 so as to recognize more fully the Canadian duality and to modify the amending formula in a way more satisfactory to Quebec. As to the Senate reform itself, a mechanism for the election of Senators is proposed, as well as two principles of a « double majority » : a first constituted of French-speaking and English-speaking Senators for a better protection of the French language, and a second made up of the Senators from Quebec and from the other provinces to deal with matters of education, culture, social affairs, communications and immigration.